Smart Air Quality Guardian: Pengawasan Polusi Udara Berbasis ESP32 dengan Sensor Gas MQ-2 dan MQ-135 - Rifki Fajar Nugraha; Fitria Nurul Husna; Sandi Sandi; Amanda Fairuz Syahla; Yogi Aldi Saputra; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2024)
The campus area of Singaperbangsa Karawang University has increased air pollution levels due to the growth of urban activities. Daily activities such as traffic, construction, and industrial activities are indicators of increased emissions of air pollutants such as PM2.5, carbon monoxide (CO), and volatile organic compounds. The lack of real-time air pollution data can hamper efforts to identify sources of pollution and take appropriate action to reduce air pollution on campus. To overcome this, solutions are needed to reduce sustainable pollutant emissions. The application of the concept of sustainable solutions is poured into research through the design of an air pollution monitoring system called Smart Air Guardian. This supervision is carried out based on a microcontroller using the MQ-2 and MQ-135 gas sensor which will monitor the air in real-time. Gas sensors MQ-2 and MQ-135 use a multilayer sensor structure that has high sensitivity to CO and CO2 content. This system is equipped with Bluetooth dual-mode capabilities and is integrated with IoT (Internet of Things) features so that it can process and display sensor data output through an LCD that easily detects air quality. The application of this system is used as an effort to monitor the air quality of the Singaperbangsa Karawang University campus to increase awareness about the importance of maintaining air quality.